2021
DOI: 10.3390/app11052237
|View full text |Cite
|
Sign up to set email alerts
|

A Low-Profile HF Meandered Dipole Antenna with a Ferrite-Loaded Artificial Magnetic Conductor

Abstract: In this paper, a low-profile HF (high-frequency) meandered dipole antenna with a ferrite-loaded artificial magnetic conductor (AMC) is proposed. To operate in the HF band while retaining a compact size, ferrite with high permeability is applied to the unit cell of the AMC. The operating frequency bandwidth of the designed unit cell of the AMC is 1.89:1 (19–36 MHz). Thereafter, a meandered dipole antenna is designed by implementing a binary genetic algorithm and is combined with the AMC. The overall size of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…The study and design of the dipole antenna structure compatible with rectangular EBG plates compared with the previous research are shown in Table 4. It was found that the study had some advantages compared to the other researches: the structural dimensions of the EBG plate, the distance from the dipole antenna to the EBG plate, except [13], 42.30 mm, and a greater gain except research [16].…”
Section: Comparison Of Researchmentioning
confidence: 92%
See 1 more Smart Citation
“…The study and design of the dipole antenna structure compatible with rectangular EBG plates compared with the previous research are shown in Table 4. It was found that the study had some advantages compared to the other researches: the structural dimensions of the EBG plate, the distance from the dipole antenna to the EBG plate, except [13], 42.30 mm, and a greater gain except research [16].…”
Section: Comparison Of Researchmentioning
confidence: 92%
“…A meandered dipole antenna for the use at 19-36 MHz was compatible with 18 × 18 units of artificial magnetic conductor (AMC) band plates. With EBG placed at a distance of 18 mm from the antenna, a gain value ranged from 22.20 to 16 dBi which radiated energy in a directional radiation pattern [16]. A shared-aperture Fabry-Perot cavity antenna (FPCA) for the use at 3.45 GHz and 5 GHz was combined with partially reflective surface (PRS), 8 × 8 units frequency selective surface (FSS) electromagnetic band plates.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, when an AMC is used as a reflector, the image current on its surface is formed in an identical direction as that of the antenna, and the phase of the incident and reflected waves are also identical; thus, the low-profile characteristics of the antenna can be achieved [17,18]. Miniaturized antennas have been proposed in the HF, VHF and UHF bands using the characteristics of the AMC [19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…The configuration of the meandered arm was optimally designed using a binary genetic algorithm, so that the antenna satisfies the VSWR characteristics of 3.5:1 or less in the HF, VHF, and UHF bands. Compared with the previous studies [19,20], the size and operating bandwidth characteristics are improved from those of the study [19], and it operates at the lowest operating frequency, lower than the antenna of the study [20]. All the simulations in this study were conducted using the CST software.…”
Section: Introductionmentioning
confidence: 99%
“…Lately, PSO has been used to solve real-world engineering problems such as the design of multilayered rectangular microstrip antenna using electromagnetic band-gap (EBG) structures [29], and bandwidth improvement of an inverted-F antenna (IFA) [30]. Furthermore, the PSO algorithm is also able to design new engineering components, for example, artificial magnetic conductors [31].…”
Section: Introductionmentioning
confidence: 99%